Pharmacological effects of natural medicine ginsenosides against Alzheimer’s disease - Shi, Zhikun; Chen, Hongyu; Zhou, Xu; Yang, Wei; Lin, Yang (Frontiers in Pharmacology, 2022)
Ginsenosides are the most important pharmacological active ingredient of ginseng, with multiple biological therapeutic targets, mild action and no side effects. It is having shown beneficial effects in vitro and in vivo models of AD. In this review, we analyze large literature, summarize the inhibition of ginsenosides fibrous extracellular deposition of β-amyloid (Aβ) and neurofibrillary tangles (NFTs) of possible mechanisms, and explain the effects of ginsenosides on AD neuroprotection from the aspects of antioxidant, anti-inflammatory, and anti-apoptosis, prove the potential of ginsenosides as a new class of drugs for the treatment of AD. In addition, according to the current clinical application status of natural drugs, this paper analysis the delivery route and delivery mode of ginsenosides from the perspective of pharmacokinetics, providing a deeper insight into the clinical application of ginsenosides in the treatment of AD.